Complement diagnostics - Frazer-Abel, Ashley (Henry Stewart Talks, 2017)
The basics and foundations of common complement tests, The current state of complement testing, Examples of the uses of the testing for patient diagnosis, The challenges confounding quality complement results, The international efforts to standardize complement analysis